Η προαγωγή της ψυχικής υγείας των μαθητών στα πλαίσια της παιδαγωγικής Waldorf - Π Κοτσαμπόπουλος; Γαλανάκη, Ε. (Παιδαγωγική Επιθεώρηση, 2018)
This paper presents a brief literature review on the impact of Waldorf education on students’ and graduates’ socio-emotional health. The main elements of Waldorf education which contribute to socio-emotional health are identified and described, namely, integration of the arts, movement and play, promoting relationships, reconnecting with nature, and spiritual development. Finally, the positive impact of Waldorf education on the reduction of attention deficit hyperactivity disorder is analyzed.